Water Absorption and Diffusivity of Germinating Seeds of Groundnut Varieties at Diffehent Soil Water Potentials - Ponkia, H P; Patel, C L; Polara, K B; Polara, J V (Annals of Arid Zone, 2016)
A laboratory experiment was conducted to evaluate the water absorption 1 and diffusivity characteristics of germinating seeds of 6 varieties of groundnut (Arachis hypogaea L.) at different soil water potentials (O.0,-O,3 and -4.0 bar) in medium black calcareous clayey soil. The rate of water absorption was measured at the interval of 5 hr after placement of seed in soil. The water uptake at a given time and total water absorption by seeds of all varieties declined with a decrease in soil water potential. Total amount of water absorbed at the time of germinati,on by seed of the same variety at different soil water potential varied considerably. The seeds of GG 11 and GAUG 10 absorbed the highest water at germination time. The seeds of JL 24 and GG 2 germinated at intermediate moisture content of seed and those of GAUG I and J II germinated at lower moisture content. The diffusivity of the seeds of most of the varieties decreased with increase in time. The average diffusivity value of most of the varieties decreased with decrease in soil water content.